Experience with ileostomy and colostomy in Crohn's disease - Post, Stefan; Herfarth, Christian; Schumacher, Hardy; Golling, Markus T.; Schürmann, Guido; Heuschen, Gundi (The British journal of surgery, 1995)
This study involved 746 patients with Crohn's disease treated surgically within a 13-year interval in whom 227 stomas (159 primary, 68 secondary) were created. The main indication (64 per cent) for primary stoma was severe perianal or genital fistulous disease. Revisional surgery for stomal complications was more common following colostomy than ileostomy (31 versus 5 per cent, P < 0.01). Twenty years after the first symptoms of Crohn's disease the cumulative risks of receiving any stoma or a permanent stoma were 41 and 14 per cent respectively. Four parameters were shown by proportional hazards analysis to be independently associated with the risk for any stoma as well as a permanent one; increased risk coincided with rectal inflammation, perianal fistula or abscess, and absence of small intestinal involvement. In addition, long-standing symptomatic disease before the first surgical intervention reduced the risk of a permanent stoma. The long-term chances of closure following temporary stoma were 75 per cent when used for ana-stomotic protection or avoidance, 79 per cent after postoperative complications, and 40 per cent for perianal or genital fistulas or for rectal inflammation or stenosis. Rectal disease and perianal fistula were the only independent predictors of a low possibility of stoma closure during follow-up.
Gesehen am 24.09.2025